Pragmatic Design of a Rectangular Printed Dipole Array Antenna for 5G Base Station - Khanet Pookkapund; Rerkchai Pukraksa; Chuwong Phongcharoenpanich; Sitthichai Dentri (My University, 2024)
This paper presents the design, fabrication and measurement of a rectangular printed dipole array antenna for 5G base stations. The antenna element is composed of a rectangular printed dipole featuring a U-shaped gap and slot positioned atop a square reflector. The measured results of the prototype antenna exhibit good agreement with simulations. The impedance bandwidth of the antenna is noteworthy, covering a substantial frequency range of 3.00 GHz - 3.82 GHz, yielding a bandwidth of 23%. The maximum gains are 6.49 dBi at a frequency of 3.5 GHz. The half-power beamwidths (HPBW) in the x-z and y-z planes are obtained to be 101.45° and 22.44°, respectively, at the frequency of 3.5 GHz. These results underscore the effectiveness of the designed rectangular printed dipole array antenna, showcasing its suitability for 5G base station applications.
Keywords: Antenna Design and Analysis; Advanced Antenna and Metasurface Technologies; Energy Harvesting in Wireless Networks